Microstructural and Mechanical Properties of CAP-WAAM Single-Track Al5356 Specimens of Differing Scale - Georgi Kotlarski; Maria Ormanova; Alexander Nikitin; Iuliia Morozova; Ralf Ossenbrink; Vesselin Michailov; Nikolay Doynov; Stefan Valkov (Machines, 2024)
The mass production of metallic components requires high agility in the working process conditioned by the necessity of building details of different shapes and sizes. Changing the size of the components theoretically influences the thermal dissipation capability of the same, which could lead to a change in their structure and mechanical properties. This is particularly important when aluminum alloys are concerned. For this reason, two Al5356 single-track specimens were built using the same technological conditions of layer deposition by varying only their geometrical size. In all cases, the specimens were wire and arc additively manufactured (WAAM) using a process based on gas metal arc welding (GMAW) in the cold arc pulse mode (CAP). The structure of both specimens was studied and defects along their surfaces were detected in the form of micro-pores and micro-cracks. A high concentration of undissolved Mg particles was also detected, along with some standalone Si particles. Uniformity in the build-up process was achieved, which led to the formation of nearly identical structures in the specimens. Subsequently, the resultant mechanical properties were also highly comparable. This indicates that the geometry-related variation in thermal conditions has an insignificant influence on the component’s structure and properties.